Moxibustion combined with Traditional Chinese Medicine ointment treatment and nursing management of a patient with low back pain caused by lumbar disc herniation (艾灸联合中药膏摩治疗1例腰痹病疼痛患者的护理体会) - QI Xiaoyu (齐笑宇); LIU Jie (刘洁); DOU Jinjie (窦金杰); LI Yuye (李玉叶); TANG Ling (唐玲); E Haiyan (鄂海燕) (中西医结合护理)
This paper summarized the treatment outcome of moxibustion combined with Traditional Chinese Medicine (TCM) ointment and nursing management of a patient with low back pain caused by lumbar disc herniation. Based on the comprehensive nursing evaluation, moxibustion and TCM ointment technology were carried out to alleviate the symptoms of low back pain and swelling pain in lower limbs. (本文总结中医特色护理技术治疗1例腰痹病疼痛患者的护理体会。在完善护理评估的基础上, 实施中医特色护理技术艾灸和中药膏摩。患者经干预后腰部疼痛及双下肢胀痛的症状缓解。)